Visual quality of life after macular hole surgery: outcome and predictive factors. Issue 4 (31st October 2006) - Hirneiß, Christoph; Neubauer, Aljoscha S; Gass, Carolin A; Reiniger, Ingrid W; Priglinger, Siegfried G; Kampik, Anselm; Haritoglou, Christos
Abstract : Background: In the present study we evaluated the functional success after macular hole surgery in correlation to visual quality of life and looked for predictive factors determining surgical success. Methods: Fifty-nine patients that underwent pars plana vitrectomy for idiopathic macular hole were included. Follow-up visits were performed in regular intervals after surgery and included a clinical examination, optical coherence tomography (OCT) and measurement of visual acuity. To assess the visual quality of life patients filled out the National Eye Institute 25-item Visual Function Questionnaire (VFQ-25) before and three months and one year after surgery. Results: Macular hole closure was achieved in 57 of 59 patients (97%). Mean visual acuity increased from 20/100 preoperatively to 20/34 one year after surgery (p = 0.02). Despite good visual acuity (20/27) in the fellow eye, visual quality of life (VFQ composite score) rose from 75.9 ± 14.4 (SD) to 81.5 ± 14.2 one year after surgery (p<0.001). Although there was no correlation between the increase in visual quality of life and visual acuity, the increase in VFQ-25 could be well predicted: low visual acuity and significant impairment on VFQ-25 testing preoperatively made patients most likely to benefit from macular hole surgery. A relatively high retinal thickness measurement at the hole border measured on OCT further increases the predictive value. Conclusion: Macular hole surgery is associated with an increase in visual quality of life despite good visual acuity of the fellow eye. Preoperative visual acuity, VFQ-25 value and partly OCT may help to predict the increase in patients' vision related quality of life after surgery.